Connexin’s Connection in Breast Cancer Growth and Progression - Debarshi Banerjee (International Journal of Cell Biology)
Gap junctions are cell-to-cell junctions that are located in the basolateral surface of two adjoining cells. A gap junction channel is composed of a family of proteins called connexins. Gap junction channels maintain intercellular communication between two cells through the exchange of ions, small metabolites, and electrical signals. Gap junction channels or connexins are widespread in terms of their expression and function in maintaining the development, differentiation, and homeostasis of vertebrate tissues. Gap junction connexins play a major role in maintaining intercellular communication among different cell types of normal mammary gland for proper development and homeostasis. Connexins have also been implicated in the pathogenesis of breast cancer. Differential expression pattern of connexins and their gap junction dependent or independent functions provide pivotal cross talk of breast tumor cells with the surrounding stromal cell in the microenvironment. Substantial research from the last 20 years has accumulated ample evidences that allow us a better understanding of the roles that connexins play in the tumorigenesis of primary breast tumor and its metastatic progression. This review will summarize the knowledge about the connexins and gap junction activities in breast cancer highlighting the differential expression and functional dynamics of connexins in the pathogenesis of the disease.